2013
DOI: 10.1590/s1806-83242013000100006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of methyl methacrylate genotoxicity by the micronucleus test

Abstract: The aim of this study was to evaluate the genotoxic potential of methyl methacrylate (MMA) vapor by simulating standard occupational exposure of 8 hours per day and using the micronucleus test. We used 32 adult male Wistar rats divided into three groups: A -16 rats exposed to MMA for 8 hours a day, B -Eight rats receiving single subcutaneous doses of cyclophosphamide on the first day of the experiment (positive control), C -Eight rats receiving only water and food ad libitum (negative control). Eight rats from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The high toxic risk of PMMA is related to the presence of a series of acrylic acid derivatives in the polymer structure, which, by diffusing from the polymer, can enhance the generation of ROS and cause genotoxicity [50][51][52][53]. A good example is experiments showing that cytogenetic and genotoxic effects were detected with the exposure of sea urchin sperm (Sphaerechinus granularis, Paracentrotus lividus) with PMMA microparticles or with extracts of this polymer [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…The high toxic risk of PMMA is related to the presence of a series of acrylic acid derivatives in the polymer structure, which, by diffusing from the polymer, can enhance the generation of ROS and cause genotoxicity [50][51][52][53]. A good example is experiments showing that cytogenetic and genotoxic effects were detected with the exposure of sea urchin sperm (Sphaerechinus granularis, Paracentrotus lividus) with PMMA microparticles or with extracts of this polymer [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Buccal micronucleus cytome (BMCyt) assay was used in this study. Other studies involving micronuclei examination of erythrocytes showed that MMA was genotoxic on day 1 of exposure, but not on day 5 [3].…”
Section: Introductionmentioning
confidence: 92%
“…They are small additional nuclei in the cytoplasm and can be seen microscopically as extranuclear DNA material [ 34 , 35 , 36 ]. MC are increasingly produced in the presence of genotoxic substances, either as a result of dysfunction of the spindle apparatus or as a result of chromosome breakage [ 32 , 36 , 37 ].…”
Section: Cytology Assessmentsmentioning
confidence: 99%